Proses Pembelajaran Materi Kekayaan Budaya Indonesia di SDN Pakel Trenggalek dengan Menggunakan Media Gambar - Cahyani, Elvima Putri Nur; Raharjo, Resdianto Permata (Jurnal Riset Madrasah Ibtidaiyah, 2024)
Teachers have an important role during the learning process in the classroom or at school. Teachers must be able to make class conditions conducive and more active or lively, and be able to make learning activities more interesting and not boring. Using appropriate learning media in the learning process can help improve student learning outcomes. Learning media is a tool used in the teaching and learning process to assist teachers in explaining material and helping students understand the material presented by the teacher. Image media is a learning medium in visual form, in the form of 2 dimensions, image media does not have sound elements but its beauty can be enjoyed. The aim of this research is to determine whether or not there is an influence of the application of image media on learning outcomes. In this research, student learning outcomes increased. The method used in this research is a quantitative method, namely a method that relies on data results from pretest, posttest, and observation.